Proliferative and Nonproliferative Lesions of the Rat and Mouse Central and Peripheral Nervous Systems: New and Revised INHAND Terms. (October 2020) - Bradley, Alys E.; Bolon, Brad; Butt, Mark T.; Cramer, Sarah D.; Czasch, Stephanie; Garman, Robert H.; George, Catherine; Gröters, Sibylle; Kaufmann, Wolfgang; Kovi, Ramesh C.; Krinke, Georg; Little, Peter B.; et al.
Harmonization of diagnostic terminology used during the histopathologic analysis of rodent tissue sections from nonclinical toxicity studies will improve the consistency of data sets produced by laboratories located around the world. The INHAND Project ( In ternational Ha rmonization of N omenclature and D iagnostic Criteria for Lesions in Rats and Mice) is a cooperative enterprise of 4 major societies of toxicologic pathology to develop a globally accepted standard vocabulary for proliferative and nonproliferative lesions in rodents. A prior manuscript ( Toxicol Pathol 2012;40[4 Suppl]:87S-157S) defined multiple diagnostic terms for toxicant-induced lesions, common spontaneous and age-related changes, and principal confounding artifacts in the rat and mouse central nervous system (CNS) and peripheral nervous system (PNS). The current article defines 9 new diagnostic terms and updates 2 previous terms for findings in the rodent CNS and PNS, the need for which has become evident in the years since the publication of the initial INHAND nomenclature for findings in rodent neural tissues. The nomenclature presented in this document is also available electronically on the Internet at the goRENI website (http://www.goreni.org/ ).